Delayed diagnosis of the full triad autoimmune polyendocrine syndrome type 2 with adrenal crisis: a case report and literature review - Yao, Zihong; Chen, Hui; Hu, Xuejian; Ge, Dan; Xu, Xiangyu; Xu, Danxia (Frontiers in Immunology, 2025)
BackgroundAutoimmune polyendocrine syndrome type 2 (APS-2) is a rare disorder characterized by autoimmune damage to multiple endocrine glands and typically involves primary adrenal insufficiency (PAI), autoimmune thyroid disease (AITD), and type 1 diabetes mellitus (T1DM). Clinical presentations that feature the full triad alongside adrenal crisis (AC) are rare, with only four such cases reported globally. While AC is the most life-threatening acute complication of APS-2, its pathogenesis is complex and incompletely understood. While there are multiple potential triggers, the role of exogenous substances such as traditional Chinese medicine [TCM] has not been systematically examined.Case presentationA 69-year-old female was hospitalized with a 9-year history of increasing fatigue, which had recently worsened due to high fever, anorexia, and vomiting lasting 2 days. She has previously been diagnosed with T1DM (nine years prior) and AITD (five years prior). Four years earlier, she underwent thymoma resection. Three years before admission, she self-administered an unknown TCM remedy that coincided with increased fatigue and mucocutaneous hyperpigmentation. On admission, she was in hypovolemic shock and severe hyponatremia (118.0 mmol/L). Laboratory tests revealed low basal cortisol (2.38 μg/dL) and markedly elevated adrenocorticotropic hormone (>1250 pg/mL). An adrenocorticotropic hormone stimulation test confirmed non-responsive adrenal function, indicating PAI. Together with her medical history and positive antibody profile, APS-2 with AC was diagnosed. She responded well to high-dose intravenous glucocorticoid therapy, sodium supplementation, and symptomatic management. Although persistent hyponatremia recurred following discharge, it resolved following fludrocortisone acetate supplementation, and her condition remained stable at the last follow-up.ConclusionWe report the fifth case of full-triad APS-2 with AC and document a 9-year diagnostic delay due to non-specific symptoms with asynchronous multi-glandular involvement. Thyroxine replacement therapy and potential TCM-induced changes may have aggravated cortisol metabolism and immune imbalances, hastening adrenal failure. Clinicians should implement stepwise organ-function monitoring in patients with any single-gland autoimmune disease, maintain vigilance for exogenous medication use, and implement multidisciplinary management strategies to mitigate the risk of AC. This case provides critical insights into both the pathogenesis and clinical management of APS-2.